Kajian Literatur Perspektif Industri dan Teknologi Komunikasi Terhadap Perkembangan Media Audio - Evinsa Injany; Indah Restasari Agustina; Nadia Farah Lutfiputri (Avant Garde, 2023)
Many people consume audio media every day, both intentionally and unintentionally. The development of communication technology, particularly the internet, has triggered the remaking of works of art, media, and the media sector. The same applies to audio media. This study attempts to investigate how concepts such as convergence, remediation, and the cultural industry affect audio media by observing the phenomenon of technological development and its impact on audio media. The three categories of audio media that are most frequently listened to by a large audience—radio, podcasts, and music—are the focus of this study. The literature review method is used in this study to find, gather, and retrieve research data. The literature review method identified 33 references relating to the growth of audio (radio, music, and podcasts), particularly in the context of Remediation, Convergence, and the Cultural Industries. In assessing the development of each sort of audio media, the perspectives of industry and communication technology are also considered. Technical advancements, the advent of the internet, and the strong rivalry among media firms have compelled the audio sector to remediate, converge, and follow the patterns of the cultural industry. The sophistication of electronic devices has also shaped the distribution patterns of the three types of audio that are synced with each other on interactive multiplatform social media. As a result, the expansion of radio, music, and podcasts has become difficult to disentangle.